2014
DOI: 10.1007/s00285-013-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Virus antibody dynamics in primary and secondary dengue infections

Abstract: Dengue viral infections show unique infection patterns arising from its four serotypes, 2,3,4). Its effects range from simple fever in primary infections to potentially fatal secondary infections. We analytically and numerically analyse virus dynamics and humoral response in a host during primary and secondary dengue infection for long periods using micro-epidemic models. The models presented here incorporate time delays, antibody dependent enhancement (ADE), a dynamic switch and a correlation factor between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 50 publications
0
42
0
2
Order By: Relevance
“…The vast majority of dengue models has focused on viral dynamics at the population‐level. Given the importance that the within‐host processes (e.g., ADE and cross‐immunity) play for both viral transmission and disease pathology, it is thus surprising that just over a handful of studies have so far investigated viral dynamics at the within‐host level (Nuraini, Tasman, Soewono, & Sidarto, ; Ansari & Hesaaraki, ; Clapham, Tricou, N. V., Simmons, & Ferguson, ; Ben‐Shachar & Koelle, ; Gujarati & Ambika, ; Nikin‐Beers & Ciupe, ; Clapham, Quyen, Kien, Dorigatti, & Simmons, ; Ben‐Shachar, Schmidler, & Koelle, ). This could, however, be explained by the little understanding we currently have about the interactions between the virus, its target cells and the host immune responses that eventually clear infection, which may also be directly responsible for clinical outcome.…”
Section: Challenges and Opportunities In Computational Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of dengue models has focused on viral dynamics at the population‐level. Given the importance that the within‐host processes (e.g., ADE and cross‐immunity) play for both viral transmission and disease pathology, it is thus surprising that just over a handful of studies have so far investigated viral dynamics at the within‐host level (Nuraini, Tasman, Soewono, & Sidarto, ; Ansari & Hesaaraki, ; Clapham, Tricou, N. V., Simmons, & Ferguson, ; Ben‐Shachar & Koelle, ; Gujarati & Ambika, ; Nikin‐Beers & Ciupe, ; Clapham, Quyen, Kien, Dorigatti, & Simmons, ; Ben‐Shachar, Schmidler, & Koelle, ). This could, however, be explained by the little understanding we currently have about the interactions between the virus, its target cells and the host immune responses that eventually clear infection, which may also be directly responsible for clinical outcome.…”
Section: Challenges and Opportunities In Computational Researchmentioning
confidence: 99%
“…() focused on the distinction between these two mechanisms and found that either could explain the data (viral and antibody titres) equally well. Two other studies have focused on the general mechanics of humoral responses (B cell and free antibody) using different modelling frameworks (Gujarati & Ambika, ; Nikin‐Beers & Ciupe, ). While one study concluded that enhancing antibodies (ADE) were key in secondary infections (Gujarati & Ambika, ), the other study suggested instead a direct decrease of overall heterologous viral clearance, whereby cross‐reactive antibodies render virions unavailable for further binding and subsequent clearance by ADCC (Nikin‐Beers & Ciupe, ).…”
Section: Challenges and Opportunities In Computational Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many mathematical studies of dengue infection. Of those, relatively few references [3,8,9,12,[16][17][18][19]21] are concerned with within-host dynamics. In all of these, it is assumed that the production of target cells (monocytes) is constant.…”
Section: Introductionmentioning
confidence: 99%